Progressive Legal Perspective on the Fulfilment of Women's and Children's Rights Post-Divorce in Divorce Cases Suitable in Religious Courts - Tijow, Lusiana Margareth (International Journal of Law Reconstruction, 2024)
A divorce filed by a wife is known as a divorce suit, is filed based on reasons permitted by Islamic law and is processed in the Religious Court according to the wife's place of residence. In divorce suit cases, women become active parties in the legal proceedings. Law Number 1 of 1974 and the Compilation of Islamic Law regulate the rights of women and children after divorce, including child support, spousal support, and mut'ah (a form of compensation for the wife). However, these regulations primarily focus on cases of divorce initiated by the husband. This research uses a qualitative method with a normative legal approach and descriptive techniques to synchronize legal regulations. The findings indicate that divorce must go through a court process to be legally valid. If mediation fails to preserve the family, the court is considered the final solution. Husbands filing for divorce are obligated to provide maintenance according to Islamic law. In cases of divorce suit, the husband cannot reconcile with the wife except through a new marriage contract. However, the implementation of women's and children's rights in divorce suit cases remains limited, influenced by the lack of claims from the plaintiff, weak implementation of Supreme Court Circular Letters, and insufficiently strong regulations. These rights are outlined in Circular Letters but have weak binding power because they are not part of formal legislation.